Die Privatbibliothek Kaiser Franz' I. von Österreich 1784-1835 Bibliotheks- und Kulturgeschichte einer fürstlichen Sammlung zwischen Aufklärung und Vormärz - Huber-Frischeis, Thomas (2011)
The former private library of Emperor Franz I (known today as "Habsburg-Iothringische Fideikommissbibliothek", housed in the Austrian National Library) is an outstanding book and graphic collction due to both the considerable extent and the exquisiteness of its holdings. This analysis is concerned with the library as a knowledge and memory institution; embedding its history in the political, social, intellectual and cultural contexts of the time.